Faktor Risiko Kejadian Anemia pada Ibu Hamil di Wilayah Puskesmas Pitu Kabupaten Ngawi - Pibriyanti, Kartika; Rizky, Aulivia Ahma; Nabawiyah, Hafidhotun; Damayanti, Amilia Yuni; Rahayu, Try; Woro, Upik; Rooiqoh, Qothrunnadaa Fajr (Puslitbang Sinergis Asa Professional, 2023)
The prevalence of anemia in Indonesia has been increasing every year. The causes of anemia during pregnancy include factors such as gestational age, pregnancy spacing, adherence to iron tablet consumption, and economic status. This study aims to analyze the risk factors for anemia in pregnant women in the Pitu Health Center area of Ngawi Regency. The research uses a descriptive analytic approach with a case-control design. The sampling technique employed is purposive sampling, with a total of 34 subjects in the case group and 34 subjects in the control group. Data analysis was conducted using three methods: univariate analysis with frequency distribution, bivariate analysis with chi-square tests, and multivariate analysis with logistic regression. The results of the univariate analysis indicate that adherence to iron tablet consumption is still low in the case group (33.5%). The bivariate analysis shows that gestational age has a p-value of 0.446, pregnancy spacing has a p-value of 1.000, adherence to iron tablet consumption has a p-value of 0.003 (OR=5.250), and economic status has a p-value of 0.031 (OR=4.060). Through multivariate analysis, it was found that adherence to iron tablet consumption (OR=5.050) has the most significant association with the occurrence of anemia in pregnant women. In conclusion, this research suggests that there is an influence of iron tablet consumption on the occurrence of anemia in pregnant women in the Pitu Health Center area of Ngawi Regency. Pregnant women who do not adhere to iron tablet consumption are 5.2 times more at risk of anemia compared to pregnant women who adhere to iron tablet consumption.